TEORI HINGGA IMPLEMENTASI KONSELING HUMANISTIK: MENGGUNAKAN EMPATI UNTUK MENDORONG KEBEBASAN DARI JERATAN NARKOTIKA - Wiyo Nuryono; Devi Ratnasari; Siti Fatimah; Nasywa Salsabila Sholihuddin; Daura Dirasyia Nadzinniya (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
Humanistic counseling with an emphasis on empathy has great potential in helping drug-addicted individuals to achieve freedom. This approach, which focuses on unconditional acceptance and deep understanding of the client's experience, can provide space for them to find better solutions to their problems. This article discusses the basic theory of humanistic counseling, including Carl Rogers' contribution in developing an empathy-based approach, and its implementation in drug addiction cases. By promoting an authentic therapeutic relationship, humanistic counseling provides emotional support that is essential for recovery. Through this approach, drug-addicted individuals can feel more valued, empowered, and motivated to continue the recovery process.